An Experimental Study of the Effects of Student Teams Achievement Division (STAD) on Vocabulary Learning of EFL Adult Learners - Ishtiaq, Muhammad; Zuraina, Ali; Salem, Muhammad (AWEJ.org, 2017)
Student Teams Achievement Divisions (STAD) has been considered as an important cooperative learning strategy in progressive pedagogy. A number of studies have supported the use of STAD in different subject areas and in different socio-cultural contexts. However, it is still an under researched area in countries like Saudi Arabia where English is taught as a Foreign Language. This quasi-experimental study was conducted in Unaizah Community College, Saudi Arabia. Both the experimental group and the control group were tested on 2000-word vocabulary test. A vocabulary test was prepared and administered by the researchers at the beginning of the experiment as a pre-test. The experimental group was taught with Student Teams Achievement Divisions (STAD) strategy whereas the control group was taught with traditional whole-class instruction method. The treatment was carried out for two weeks. At the end of the experiment, the same vocabulary test was re-administered as a post-test. Independent samples t-test was used to analyze the data using SPSS 21. Results showed that there was a significant difference between the experimental group and the control group in favor of the experimental group (p=0.002 < 0.05).